Radioresistance of Deinococcus radiodurans: functions necessary to survive ionizing radiation are also necessary to survive prolonged desiccation. - Mattimore, V (1996)
Forty-one ionizing radiation-sensitive strains of Deinococcus radiodurans were evaluated for their ability to survive 6 weeks of desiccation. All exhibited a substantial loss of viability upon rehydration compared with wild-type D. radiodurans. Examination of chromosomal DNA from desiccated cultures revealed a time-dependent increase in DNA damage, as measured by an increase in DNA double-strand breaks. The evidence presented suggests that D. radiodurans' ionizing radiation resistance is incidental, a consequence of this organism's adaptation to a common physiological stress, dehydration.